Macroprudential policy in the New Keynesian world - Hans Gersbach; Volker Hahn; Yulin Liu (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
We integrate banks and the coexistence of bank and bond financing into an otherwise standard New Keynesian framework. There are two policy-makers: a central banker, who can decide on short-term nominal interest rates, and a macroprudential policy-maker, who can vary aggregate capital requirements. The two policy instruments can be used to stabilize shocks, to moderate bank credit cycles, and to induce a more efficient allocation of resources across sectors. Moreover, we investigate the optimal combination of simple policy rules for interest rates and capital requirements. The optimal policy rules imply that the central bank should focus exclusively on price stability and the macroprudential policy-maker should react exclusively to changes in loan rate premia.
Keywords: E520; E580; G280; 330; central banks; banking regulation; capital requirements; optimal monetary policy